The Role of Data Analytics in Optimizing Digital Marketing Strategies in the Digital Technology Era - Ernawati, Ayu (Pasundan Social Science Development, 2025)
In the ever-evolving digital technology era, the role of data analytics has become increasingly vital in optimizing digital marketing strategies. Data analytics enables marketers to gain deeper insights into consumer behavior, allowing them to make more informed and targeted decisions. Through the use of big data, machine learning, and advanced analytics algorithms, companies can identify market trends, consumer preferences, and areas that need improvement in their marketing strategies. Data analytics also facilitates the personalization of marketing messages, improving conversion rates and customer loyalty. Furthermore, analytics technologies provide real-time insights, enabling swift decision-making and responsiveness to changing market dynamics. On the other hand, challenges in implementing data analytics include the need for adequate technological infrastructure, data analysis skills, and the safeguarding of consumer data privacy and security. Therefore, integrating data analytics into digital marketing strategies requires special attention to both technical and ethical aspects. With proper utilization, data analytics can serve as a highly valuable tool in enhancing the effectiveness and efficiency of digital marketing.